The therapeutic potential of sulforaphane on light-induced photoreceptor degeneration through antiapoptosis and antioxidant protection. (November 2016) - Kong, Li; Liu, Bo; Zhang, Chenghong; Wang, Bing; Wang, Hongfei; Song, Xiaoxia; Yang, Yang; Ren, Xiang; Yin, Liangwei; Kong, Hui; Ma, Haiying
Abstract: Oxidative stress due to excessive light exposure can exacerbate a variety of human retinal diseases by accelerating photoreceptor cell death. The thioredoxin (Trx) system is considered to play a crucial role in reduction/oxidation (redox) regulation of signal transduction and in cell defense against oxidative stresses. Sulforaphane (SF) protects cells from oxidative damage through nuclear factor (erythroid-derived 2)-like 2 (Nrf2), which is responsible for multiple detoxification processes, including elevating the expression of Trx. This study sought to demonstrate whether SF increased Trx expression in retinal tissues in vivo and whether it could preserve the photoreceptors from degeneration induced by oxidative stress. Our data clearly showed that pretreatment with SF abated photoreceptor cell loss, in association with increased expression of Nrf2 and Trx, subsequently activating the Ras/Raf1/Erk signaling pathway and decreasing the expression of Bak1, Cyt-c release and the activity of caspase-3 in light-induced mouse retinas. These data suggested that the therapeutic potential of SF in retinal degeneration due to oxidative stress might partially involve anti-caspase and antioxidant protection mediated by Trx. Highlights: Pretreatment with sulforaphane abates photoreceptor cell loss in retinal light damage. Sulforaphane leads to increase expression of Nrf2 and Trx. Sulforaphane decreases expression of Bak1, release of Cyt-c and the activity of caspase-3. The underlying mechanism might partially involve antiapoptotic and antioxidant protection of sulforaphane.